2015
DOI: 10.1016/j.ijmm.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the Chlamydia trachomatis inclusion does not require bacterial replication

Abstract: Chlamydia trachomatis replication takes place inside of a host cell, exclusively within a vacuole known as the inclusion. During an infection, the inclusion expands to accommodate the increasing numbers of C. trachomatis. However, whether inclusion expansion requires bacterial replication and/or de novo protein synthesis has not been previously investigated in detail. Therefore, using a chemical biology approach, we herein investigated C. trachomatis inclusion expansion under varying conditions in vitro. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 25 publications
2
32
0
2
Order By: Relevance
“…This counterintuitive finding is supported by a recent report that showed that C. trachomatis replication does not necessarily correlate with inclusion size, even in immortalized cells (50).…”
Section: Discussionmentioning
confidence: 64%
“…This counterintuitive finding is supported by a recent report that showed that C. trachomatis replication does not necessarily correlate with inclusion size, even in immortalized cells (50).…”
Section: Discussionmentioning
confidence: 64%
“…As it is shown in the images, there was a complete recovery of the size of the inclusions when the inhibitor was removed (Figure 2E,F). Chlamydial inclusion expansion precedes bacterial replication (Engström et al, 2015), therefore to directly assess bacterial viability and development after the strongest iAkt treatment (10 μM, 24 h, 37°C), we performed progeny/reinfection assays. Results show a significant recovery in the amount of infectious organisms after the removal of the inhibitor, notwithstanding, the inclusion forming units did not reach the levels of untreated cells (Figure 2G).…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with a recent report indicating that chlamydial protein synthesis, but not chlamydial replication, is required for normal expansion of C . trachomatis inclusions [ 40 ]. It can thus be speculated that the DAMP-dependent reduction of inclusion size observed for C .…”
Section: Discussionmentioning
confidence: 99%